Surgical Pathology of Liver Tumors - Mounajjed, Taofic; Chandan, Vishal S.; Torbenson, Michael S. (Springer International Publishing : Imprint: Springer, 2015)
This text provides a practical guide for the diagnostic surgical pathologist in evaluating tumors involving the liver. It comprehensively covers the histological findings and key clinical and molecular correlates of liver tumors. The focus is on material that is most relevant to the actual practice of liver pathology including those aspects that are directly relevant to the diagnosis, subtyping, and prognostication of hepatic adenomas specimens, including biopsy specimens and surgical resections. The book will teach pathologists how to avoid common diagnostic pitfalls. Each chapter uses or discusses the nomenclature and classification system of liver tumors as per the current WHO classification of liver tumors. Each chapter fully incorporates the most up-to-date diagnostic methodologies, including immunohistochemistry and molecular methods. The text is richly illustrated with beautiful color images that highlight not just the "average" histological findings for a given entity, but also fully illustrate all of the key histological variability. Gross images are also included to highlight important diagnostic features. Tables are used judiciously to present summary information that allows a quick review on how similar entities compare and contrast. In addition, the clinical significance of various diseases are discussed in a focused fashion that highlights how pathology information is being used to make key clinical management decisions.  Surgical Pathology of Liver Tumors will be of great utility to surgical pathologists and surgical pathologists in training as well as clinicians involved in the care of patients with liver tumors, particularly hepatologists and oncologists.